UNCERTAINTY AVOIDANCE, RISK AVOIDANCE AND PERCEIVED RISK: A CULTURAL PERSPECTIVE OF INDIVIDUAL INVESTORS - Imran Arshad; Yusnidah Ibrahim (Hasanuddin Economics and Business Review, 2019)
Risk serves as an important aspect that can change the decision making of individuals, especially if it is related to investment decision making. The effects of risk on investment decision making have been extensively discussed in the literature but little of it assessed the dominance of various risk-related factors in investment decision making by individuals. In order to make up for this lack,  this research studies the impact of risk avoidance,  uncertainty avoidance and perceived risk on the investment intentions of individual investors in Pakistan and relate it to Hofstede’s cultural dimension. The data was collected from individual investors and after screening, a sample of 548 was found useable for further analysis. Using SEM-PLS, it was found that risk avoidance and uncertainty avoidance significantly influence the investment intention of individual investors. On the other hand perceived risk does not influence the investment intentions of individual investors. In the evaluation of dominating factors, it was found that   risk avoidance is the most significant and the strongest factor that influences the individual investors’ investment intentions. This paper suggests that investment managers should work on strategies to change the risk avoidance behaviour of investors. Moreover, findings suggest that the cultural aspect is more important, and the level of risk avoidance should be kept in mind while offering stocks in the market. The Security Exchange Commission of Pakistan can prepare risk-adjusted products to enhance the level of intentions among the individual investors in Pakistan.